FAKTA SEJARAH DALAM NOVEL DHARMAGANDUL KARYA SRI WINTALA ACHMAD (KAJIAN NEW HISTORICISM) - Mustika Mustika; Elmy Selfiana Malik (Journal Idea of History, 2019)
This research aims to describe the historical facts in the novel of Dharmagandul by Sri Wintala This study aims to describe the historical facts in the novel of Dharmagandul by Sri Wintala Achmad which was set in the Majapahit Kingdom. The novel was examined using the New Historicism approach, which used non-literary texts combined with literary texts to be analyzed. The procedures of this study included: (1) parallel reading techniques, namely techniques performed by reading literary texts (novels) with non-literary texts; (2) the analysis used includes data presentation and discussion. The analysis used in studying the novel Dharmagandul by Sri Wintala Achmad was paralleled by non-literary texts relating to events in the novel; and (3) presentation of the conclusions from the results of the analysis. The results of the study included: (1) the applying of Dyah Pitaloka by Patih Gajah Mada to Prabu Hayam Wuruk; (2) Wikramawardhana's post-HayamWuruk power; (3) Paregreg war; and (4) Sri Ratu Suhita's revenged against Raden Gajah. The results of the study of historical facts in the novel Dharmagandul are expected to provide knowledge that literature can be born from historical reality and this research is expected to be a lesson for the people of Indonesia to not repeat the bitter events that have occurred during the Majapahit kingdom. Keyword: historical facts, Dharmagandul, new historicism, Majapahit